2022
DOI: 10.3390/app121910077
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Forest Burned Area Detection with Various Input Variables: A Case Study of South Korea

Abstract: Recently, an increase in wildfire incidents has caused significant damage from economical, humanitarian, and environmental perspectives. Wildfires have increased in severity, frequency, and duration because of climate change and rising global temperatures, resulting in the release of massive volumes of greenhouse gases, the destruction of forests and associated habitats, and the damage to infrastructures. Therefore, identifying burned areas is crucial for monitoring wildfire damage. In this study, we aim at de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…However, in Area N, the detection performance was reduced owing to the mixed terrain comprising urban and forest areas. The findings are similar to those of a previous study [37]. Knopp et al [36] also reported that misclassification occurs in specific LC types, such as dark coastal areas, agricultural lands, and volcanic rocks, which appear as burned areas.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, in Area N, the detection performance was reduced owing to the mixed terrain comprising urban and forest areas. The findings are similar to those of a previous study [37]. Knopp et al [36] also reported that misclassification occurs in specific LC types, such as dark coastal areas, agricultural lands, and volcanic rocks, which appear as burned areas.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we evaluated different spectral bands and indices as well as ML and DL algorithms for automated burned area detection using Sentinel-2 single-temporal satellite imagery. Our results were comparable with those of previous studies on DL input channels [37,38], and it was confirmed that even when single-temporal images were used, high detection performance can be achieved if a high-quality dataset is available. However, the application of SI to a single image to represent forest fire damage showed a relatively low improvement in accuracy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our next step consisted of calculating the NBR for the pre-fire and post-fire periods in each area using Equation (1). To emphasize the burned areas, we computed the differenced dNBR and applied the United States Geological Survey (USGS) wildfire severity classification system based on the dNBR values [64], as shown in the following Table 4.…”
Section: Processing Stepsmentioning
confidence: 99%
“…Our next step consisted of calculating the NBR for the pre-fire and post-fire periods in each area using Equation (1). To emphasize the burned areas, we computed the differenced dNBR and applied the United States Geological Survey (USGS) wildfire severity classification system based on the dNBR values [64], as shown in the following Table 4. We marked sample points in areas that experienced vegetation changes based on preand post-fire image visualization, as well as FIRMS data, GLAD data, and USGS classification in Tangier.…”
Section: Severity Colormentioning
confidence: 99%